Urban-suburban differences in the demographics and clinical profiles of type 2 diabetic patients attending primary healthcare centres in Malta - Tania Cardona; Neville Calleja; Glorianne Pullicino (James Cook University, 2020)
Introduction: Social factors might bring about health inequities. Vulnerable population groups, including those suffering from non-communicable diseases such as type 2 diabetes and depression, might be more prone to suffering the effects of such inequities. This study aimed to identify patients with type 2 diabetes with depression in a primary care setting, with the objective of describing health inequities among urban and suburban dwellers. Methods: A quantitative, retrospective and descriptive study was carried out among patients with diabetes attending public primary healthcare centres in different regions of Malta. Participants completed a self-administered questionnaire to identify patient and disease characteristics. Convenience sampling was used. Results: The logistic regression model predicting the likelihood of different factors occurring with suburban patients with diabetes as opposed to those residing in urban areas contained five independent variables (severity of depression, monthly income, blood capillary glucose readings, weight and nationality). The full model containing all predictors was statistically significant, c2 (5, n=400), p<0.001, indicating that the model was able to distinguish between urban and suburban areas. The model as a whole explained between 10% (Cox and Snell R2) and 20% (Nagelkerke R2) of the variance in urban and suburban areas, and correctly classified 73.8% of cases. All five of the independent variables made a unique, statistically significant contribution to the model. Elevated blood glucose and obesity tended to be more prevalent in suburban respondents than in urban participants. Conversely, participants with diabetes living in urban areas were more likely to be depressed, non-Maltese and have a higher income. Conclusion: Despite the small size of the Maltese islands and the expected social homogeneity, health inequities still exist, highlighting the importance of social factors in the epidemiology of disease. This study provides information for healthcare professionals and policy-makers to mitigate the effects of social inequities on vulnerable population groups.